The socio-economic effects of covid-19 - Mahagamage, Yohan; Marasinghe, Kalpani (Saúde e Sociedade, 2023)
The covid-19 epidemic has spread rapidly all around the world since December 8, 2019, from China, the world’s largest exporter of goods. The outbreak quickly spread throughout the countries, affecting the health sector, and causing economic, environmental, and social challenges. Therefore, the article discusses the impacts of covid-19, to provide a better understanding to the public and the researchers regarding its impact on the society, education, communication, and economy of infected countries. The study followed a qualitative case study approach, including literature review and document analysis. The review was done on a wide range of data sources including journal articles, books, government documents, newspaper articles, and policy reports. The covid-19 is rigorously disrupting the global economy and almost all countries are trying to slow down the spread of the disease by increasing the testing, facilitating treatments of infected patients, quarantining suspected cases via contact networks, implementing social distancing by restricting large gatherings, maintaining countrywide or partial lock down, and etc. However, these aspects are highly challenging to the maintenance of the society’s daily life and addressing difficulties raised by the public to implement correct strategies to face the pandemic situations globally is necessary.